PENERAPAN METODE DISKUSI KELOMPOK UNTUK MENINGKATKAN HASIL BELAJAR IPA DAN AKTIVITAS SISWA KELAS IV SD I SIDOREKSO PADA MATERI MENGGOLONGKAN HEWAN BERDASARKAN JENIS MAKANANNYA - Malik, Jamaludin (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2019)
The purpose of this study was to determine the improvement of learning outcomes of science materials classifying animals based on the type of food using group discussion methods in fourth grade students of SD 1 Sidorekso as well as to improve student learning activities especially in the first semester of 2015/2016 science lessons. The research method used is classroom action research. The research subjects were 27 students. Data collection techniques using the test method. The analysis technique goes through two stages, namely 1) using comparative descriptive analysis techniques and 2) using observation techniques with descriptive analysis based on the results of observation and reflection. The study carried out two cycles from July to September 2015. Each cycle includes four stages of activity, namely planning (planning), implementing actions (acting),observing (observing) and reflection (reflecting). The results showed that the learning outcomes of science about classifying animals based on their type of food using group discussion methods in fourth grade students of SD 1 Sidorekso could increase. From the initial conditions, the average formative test score is 61.48 with the percentage completed 29.63% and the percentage of tifak complete 70.37%. The results of the first cycle increased by an average of 68.15 with a complete percentage of 66.67% and the percentage did not complete 33.33%. The results of the second cycle rose to 73.70 with the percentage completed 96.30% and the percentage did not complete 3.70%. Conclusion of group discussion methods can improve science learning outcomes and student activities.